Ectopia Lentis ? Etiology and Management in Children - Sabrina Sharif, Zahid Dogar, Seema Qayyum, Ajmal Chaudhary, Majid Hussain, Asma Mushtaq (Pakistan Journal of Ophthalmology, 2016)
Purpose: To study the etiology, mode of presentation and management strategies of ectopia lentis in children less than 10 years of age. Study Design: interventional case series Place and Duration of Study: The study was conducted in the department of pediatric ophthalmology, The Children’s Hospital and Institute of Child Health, Lahore and department of ophthalmology, KEMU, Lahore from January 2010-January 2015. Material and Methods: All patients diagnosed as having non-traumatic ectopia lentis were included in the study. The children were evaluated for vision threatening complications of ectopia lentis. A complete systemic examination was done by the pediatrician to diagnose any associated inherited systemic syndrome. The family members of the child were also examined for ectopia lentis. Surgery was planned in all eyes where there was displacement of the lens in anterior chamber with or without pupil block. Results: A total of 54 eyes of 27 patients diagnosed as having non-traumatic ectopia lentis were included in the study. There were 15 males, 12 female patients with 24 patients falling in the age bracket of 0 – 7 years. Seventeen out of the twenty – seven patients were diagnosed as having inherited systemic syndrome, Marfan being the most common. Majority of the patients presented to the eye department only when there was pain in the eye due to increase in IOP. Conclusion: Every child patient with ectopia lentis is a candidate for a thorough ocular and systemic examination for early recognition of vision threatening as well as life threatening systemic problems. The importance of involvement of parent with amblyopia management cannot be overemphasized for visual rehabilitation of the child. Key words: Ectopia lens, subluxation of lens, Lensectomy.